Legal Clarification On The Use Of Basements In The Context Of Public Land Acquisition In Indonesia - Diyan Isnaeni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Rapid urban growth and increasing infrastructure needs in Indonesia are driving an increasing need for basement use. Even so, significant legal challenges arise, especially with regard to rights to the crypt and conflict resolution mechanisms. The lack of clarity in the basic agrarian law and the law on Land Acquisition for the public interest creates the potential for conflict and social injustice in the procurement and use of basements. This study conducted a normative legal analysis of the agrarian Basic Law and the land acquisition law for the public interest, and evaluated how these laws operate in practice. Through a philosophical and analytical approach, the study considers the underlying legal principles and evaluates the effectiveness of existing regulation and enforcement. In seeking a solution to this challenge, the study considers a range of measures, including legal reform to provide further clarification on the right to a basement; development of effective and fair conflict resolution mechanisms; and increased protection of the rights and interests of landowners in the process of land acquisition. These solutions will be tailored to the local context and needs and involve the participation of all interested parties. This research seeks a deeper understanding of how laws operate in this context and evaluates whether existing laws are sufficient and effective in regulating these issues. The results of this study are expected to make an important contribution in formulating and updating legal regulations on the use of basements in the context of land acquisition for public use in Indonesia.